Terminal deletion of chromosome 13 in a fetus with normal NIPT: The added value of invasive prenatal diagnosis in the NIPT era - Evy Vervecken; Bettina Blaumeiser; Tina Vanderheyden; Jan Hauspy; Katrien Janssens (Clinical Case Reports, 2020)
Abstract In the age of noninvasive prenatal testing, there is still an important role for invasive prenatal diagnosis, even for chromosomes 13, 18, and 21.